(untitled) (Biological Sciences - PJSIR, 2008)
Engineering bore logs of 86 holes, installed in the Sirajgonj town of Bangladesh and adjoining areas, were used to identify the geotechnical characteristics of the sub-surface sediments. The study area was divided into four major zones on the basis of surface and sub-surface geological characters, engineering properties of soil, such as lithology, atterberg limit, consistency, SPT, bearing capacity, plasticity, compaction, consolidation and compressibility etc., and geotechnical map. Each zone can be used for different types of construction purposes, characterized by specific engineering properties. Detailed engineering geological information should be used for sustainable land-use planning and development to reduce environmental hazards